High Harmony, Low Freedom: The Measurement Paradox of Religious Moderation in Indonesia - Muhammad Nur (Punggawa Global Research: Jurnal Multidisiplin, 2026)
Indonesia’s religious moderation agenda has gained strong institutional support through policy documents, educational programs, and national measurement instruments. The 2025 Religious Harmony Index recorded a high score of 77.89, suggesting that interreligious coexistence remains broadly stable. At the same time, reports on freedom of religion or belief continue to record restrictions, contested houses of worship, unequal administrative treatment, and weak protection for minority communities. Drawing on qualitative documentary research and descriptive-comparative analysis of secondary data, this study examines the gap between harmony-based measurement and rights-based evidence. The findings argue that high harmony and low freedom can coexist because they are produced through different evidentiary logics. Harmony indicators mainly capture perception, social acceptance, and cooperation, while rights-based reports record access, obstruction, actors, affected communities, and institutional responses. The measurement paradox appears when harmony is treated as a proxy for religious freedom. A more credible evaluation of religious moderation requires a paired reading of social coexistence and rights enforcement, especially where minority rights become locally contested and administratively difficult to protect.